Chronic Liver Disease: Liver Cirrhosis and Diagnostic Features: Liver Cirrhosis and Diagnostic Features - Junaid Dar, Ali; John, Akash; Ali, Abid; Ansar, Arooj; Azam, Sheza (Pakistan Journal of Health Sciences, 2023)
Chronic Liver diseases can cause liver cirrhosis, a late stage when the normal liver tissue becomes scar tissue, irreversibly damaging liver. Objective: To determine the causes of liver cirrhosis in different patients using computed tomography (CT). Methods: It is a cross-sectional study conducted in the Radiology Department of Private Hospital Gujrat, Pakistan from 1, August 2022 to 30, November 2022. Abdominal non-contrast CT of the patients was performed in a supine position. A sample size of 82 patients has been calculated via a convenient sampling technique using a mean approach from previous related articles. Patients with renal stones on CT KUB were excluded. The data was analyzed using SPSS version 26. Results: Liver cirrhosis seen to be more common in men 65(79.3%) than women 17(20.7%). Liver cirrhosis is seen to be more common at the age of 30-39years 51(62.2%), followed by 40-49years 29(35.4%), and 18-29years 2(2.4%). Most common cause of liver cirrhosis is hepatitis C 39(47.6%). The most common symptom in liver cirrhosis is loss of appetite 34(41.5%), followed by weight loss 23(28.0%). The most common finding is a change in liver volume 33(40.2%), followed by coarse liver 26(31.7%). Conclusions: Liver cirrhosis is seen commonly in men in the age range of 42 to 54 years. The most common symptoms of liver cirrhosis are loss of appetite followed by weight loss. One of the best modalities to rule out chronic liver disease specifically liver cirrhosis is CT scan.